Chapter 2 Group Psycho-Emotional Dynamics as Central to Effective Institutional Change Connecting Individual and Whole-Institution Approaches - Jackson, Jennifer Kasi; O Anderson, Amena; Nolan, James; Holmes, Maja; Kunkle, Christine; Dilks, Lisa (Taylor & Francis, 2023)
Diversifying the academic faculty remains an elusive goal marked by slow and uneven progress. This book describes an effective model for institutional transformation which is uniquely grounded in group-level processes. Efforts at institutional transformation continue to center individual actors. This is evident in the proliferation of programs that train individuals on implicit bias, search strategies, and other diversity and inclusion-based content as solutions for inequities in academia. Acknowledging the value of these approaches, this book adds a new focus: group-level processes. It unifies research on gender and racial inequity with concepts from social psychological theories of group dynamics to present a model of change centered on professional adult learners, including faculty and academic staff. The book details the implementation of group-level processes based on insights from the learning sciences, higher education leadership, communication studies, and group facilitation to instill norms for a more equitable and inclusive institution. Drawing on quantitative and qualitative data to illustrate the impact of group-level initiatives, the book offers recommendations to enable the application of this model in higher education contexts. This book will be of interest to researchers and graduate students studying institutional transformation, academic social justice leadership, and faculty professional development and to those interested in integrating justice and equity into team science, translational research, and other trans-, inter-, and multi-disciplinary fields.